Detecting TB Cases among Household Contacts of Patients with Pulmonary TB through Active Contact Tracing in the Arsi Zone, Ethiopia. (4th October 2017) - Tufa, Tafese Beyene; Nordmann, Tamara; Bosselmann, Matthias; nfeld, Andreas Schö; Fuchs, André; Feldt, Torsten; Häussinger, Dieter
Abstract: Background: WHO and Ethiopian guidelines suggest contact investigation for all household contacts of index cases with pulmonary TB (PTB). However it is not routinely exercised in the local setting. Therefore, the objective of this study was to identify TB and MDR-TB cases among household contacts of patients with PTB. Methods: All patients newly diagnosed with PTB at Asella Teaching Hospital (ATH) and six of its surrounding health centers were considered as index cases and enrolled in the study after giving informed consent. Each household member of index patients was actively screened for TB using a standardized questionnaire. If pulmonary TB was suspected two sputum samples for each suspect contact were examined, both microscopically and with GeneXpert©. Contact persons with symptoms of extra-pulmonary TB were referred to ATH for further investigations. Results: Between August 2015 and August 2016 a total of 144 index patients were enrolled in the study. Of those, 90 had smear-positive PTB and 54 had smear-negative PTB. Among 100 positive samples in GeneXpert©, 4 were tested positive for rifampicin resistance. Of these, three of them were confirmed to be MDR-TB by culture method. A total of 601 household members were screened for signs and symptoms of TB. Eighty-two (13.6%) suspected PTB cases underwent sputum investigation. Seven household contacts (1.2%) were diagnosed with active TB-disease and put on anti-TB treatment. Of those, five cases were confirmed with GeneXpert© and culture, and in two cases the diagnosis was made by chest X-ray. Conclusion: Through active contact tracing, we found 1.2% prevalence of undiscovered TB among household members of index patients. We also found 4% of MDR-TB among index patients who would have not been suspected for MDR-TB according to the national guideline recommendation. We recommend cost-benefit analysis studies for the use GeneXpert© for all smear positive PTB cases to tackle the expansion of MDR-TB. Disclosures: All authors: No reported disclosures.